Comparison of emotional intelligence on sport coaches - Nikbakhsh, R.; Nourollahi, H.; Mirzaei, A.; Rahimi, M. (European Journal of Experimental Biology, 2014)
The main purpose of this study was to comparison of emotional intelligence on sport coaches. The population of the study consisted of 1677 women and 2291 men that 313 women 327men was selected through sample sampling method. The Syber Yashring (1986) questionnaire for emotional intelligence is used in this research. The result indicates that there was a not significant difference on emotional intelligence among men and women. Also, there was significant significant relationship between emotional intelligence with age, sport experience and coaching experience.